Influence of the type of lipids of the diets on fatty acid composition of adipose tissue and muscle in sheep - Bas P.; Morand-Fehr P.; Sauvant D. (Nutrition and feeding strategies of sheep and goats under harsh climates, 2004)
The fatty acid contents and profiles of adipose tissues and muscles influence the characteristics of meat quality. The variations of the fatty acid composition of these deposits have been studied by meta-analysis of published data, in relation with types of lipids contained in the diets. With diets rich in non fat-supplemented concentrate, the percentages of C18:0 and C18:3 were lower and the percentages of C18:1 and C18:2 were higher in the adipose tissues and in the muscles than with forage-based diets. The supplementation of diets with vegetable fat produced adipose tissues and muscles with a higher level of monounsaturated and polyunsaturated fatty acids compared to animal fat. Each fat source induced a specific answer in lipid tissues which depended on the lipid composition of the diet.
9. Seminar of the Sub-Network on Nutrition of the FAO-CIHEAM Inter-Regional Cooperative Research and Development Network on Sheep and Goats, 2001/11/08-10, Hammamet (Tunisia)